2011
DOI: 10.1017/s0066154600008760
|View full text |Cite
|
Sign up to set email alerts
|

They wrote on wood. The case for a hieroglyphic scribal tradition on wooden writing boards in Hittite Anatolia

Abstract: The wooden writing boards frequently mentioned in Hittite texts have given rise to much debate, mostly regarding the scale on which they were used and the type of script that was written on them (cuneiform or hieroglyphs). In this paper, the evidence for the use of wooden writing boards in Hittite Anatolia will be (re-)evaluated. It will be argued that they were used for private and economic documents, and that they were written on in Anatolian hieroglyphs. Important indications of this are the distinct terms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(5 citation statements)
references
References 17 publications
0
4
0
1
Order By: Relevance
“…Writing-boards, made of wood and covered in a wax writing surface, are not directly attested at Ugarit, but there is every reason to believe they were in use there, as they are likely to have been across much of the region (Cammarosano et al 2019). Famous examples are known from Neo-Assyrian Nineveh and Nimrud (Symington 1991), but probably more relevant are the board found in the Uluburun shipwreck alongside a largely Levantine cargo (Payton 1991) and the numerous references in Hittite texts to writing on wood (Waal 2011). A letter sent to Ugarit from the Middle Euphrates region mentions a ‘tablet of wax’ (RS 19.53: Cammarosano et al 2019, 131; Symington 1991, 121) and a pictorial stele found on Ugarit's acropolis has been interpreted as showing a treaty-signing ceremony, with two folded writing-boards on a table (Cammarosano et al 2019, 131; Postgate 2013, 401–2).…”
Section: Writing-boardsmentioning
confidence: 99%
“…Writing-boards, made of wood and covered in a wax writing surface, are not directly attested at Ugarit, but there is every reason to believe they were in use there, as they are likely to have been across much of the region (Cammarosano et al 2019). Famous examples are known from Neo-Assyrian Nineveh and Nimrud (Symington 1991), but probably more relevant are the board found in the Uluburun shipwreck alongside a largely Levantine cargo (Payton 1991) and the numerous references in Hittite texts to writing on wood (Waal 2011). A letter sent to Ugarit from the Middle Euphrates region mentions a ‘tablet of wax’ (RS 19.53: Cammarosano et al 2019, 131; Symington 1991, 121) and a pictorial stele found on Ugarit's acropolis has been interpreted as showing a treaty-signing ceremony, with two folded writing-boards on a table (Cammarosano et al 2019, 131; Postgate 2013, 401–2).…”
Section: Writing-boardsmentioning
confidence: 99%
“…Our knowledge of Hittite religion is largely limited to the operations at the governmental level described in these documents, since the cuneiform archives of Hatti were produced exclusively by and for the use of the royal bureaucracy. Wooden tablets-which of course have not survived-were also in use among the Hittites and it has often been suggested that economic records and other documents of the general population were inscribed in this medium (see Waal 2011). That is, we know next to nothing of the worship or spiritual lives of non-elite persons in Hatti.…”
Section: The Sourcesmentioning
confidence: 99%
“…Waal 2011. Waal also raises the possibility that the Hittite boards may not have been wax-covered, with the writing being made directly on wood with ink, similar to examples from Egypt or Roman Vindolanda.…”
mentioning
confidence: 99%